2017
DOI: 10.1016/j.nbd.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain knock-out of torsinA reduces striatal free-water and impairs whole-brain functional connectivity in a symptomatic mouse model of DYT1 dystonia

Abstract: Multiple lines of evidence implicate striatal dysfunction in the pathogenesis of dystonia, including in DYT1, a common inherited form of the disease. The impact of striatal dysfunction on connected motor circuits and their interaction with other brain regions is poorly understood. Conditional knock-out (cKO) of the DYT1 protein torsinA from forebrain cholinergic and GABA-ergic neurons creates a symptomatic model that recapitulates many characteristics of DYT1 dystonia, including the developmental onset of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Corroborating these findings, an ex vivo study in the heterozygous DYT1 knock-in mouse model showed reduced connectivity of the cerebello-thalamic, thalamo-cortical and thalamo-striatal pathways in mutants compared to wild type (Ulug et al, 2011). Another study reported deficits of free water diffusivity and widespread increases in functional connectivity of the stratum with somatosensory cortex, thalamus, cerebellum and brainstem in the conditional knock-out mice of the DYT1 protein torsinA (DeSimone et al, 2017). As the cerebello-thalamo-cortical pathway facilitates intracortical inhibition via projections to interneurons in the sensorimotor cortex (Molinari, Filippini, & Leggio, 2002), these findings may suggest the presence of the intermediary pattern in non-manifesting carriers that may act as a buffer against the aberrant outflow from the proximal part of this pathway (Niethammer, Carbon, Argyelan, & Eidelberg, 2011).…”
Section: Structural Neuroimaging Of Dystoniamentioning
confidence: 99%
“…Corroborating these findings, an ex vivo study in the heterozygous DYT1 knock-in mouse model showed reduced connectivity of the cerebello-thalamic, thalamo-cortical and thalamo-striatal pathways in mutants compared to wild type (Ulug et al, 2011). Another study reported deficits of free water diffusivity and widespread increases in functional connectivity of the stratum with somatosensory cortex, thalamus, cerebellum and brainstem in the conditional knock-out mice of the DYT1 protein torsinA (DeSimone et al, 2017). As the cerebello-thalamo-cortical pathway facilitates intracortical inhibition via projections to interneurons in the sensorimotor cortex (Molinari, Filippini, & Leggio, 2002), these findings may suggest the presence of the intermediary pattern in non-manifesting carriers that may act as a buffer against the aberrant outflow from the proximal part of this pathway (Niethammer, Carbon, Argyelan, & Eidelberg, 2011).…”
Section: Structural Neuroimaging Of Dystoniamentioning
confidence: 99%
“…The loss of torsinA function in either the cerebral cortex or cerebellum result in motor dysfunction (DeSimone et al, 2017; Fremont, Tewari, Angueyra, & Khodakhah, 2017; Yokoi, Dang, Mitsui, Li, & Li, 2008), indicating a neuronal component of TOR1A’s function in dystonia. Based on these observations, we examined the 195 genes that carry candidate ΔE mutation modifiers for their association with neuropsychiatric and neuromuscular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the differential expression pattern of Torsins likely contributes to the tissue-specific manifestation of TorsinA∆E-linked pathology. Indeed, phenotypes similar to DYT1 dystonia-specific symptoms were observed in conditional mouse models upon deletion of TorsinA in individual brain regions [47][48][49]. These symptoms manifest as abnormal posturing and dystonia-like twisting motions, as well as neurodegeneration of select regions of the central nervous system.…”
Section: Torsin Assemblies and Dystonia Movement Disordersmentioning
confidence: 91%
“…In addition, TorsinA deletion or depletion causes dystonic symptoms even in animal models that do not express TorsinA∆E [47,49,53]. In fact, a mildly beneficial effect of expressing TorsinA∆E relative to a Torsin deletion was observed both in animal models [47,48] and tissue culture models [30], suggesting that TorsinA∆E may act as a hypomorphic allele.…”
Section: Torsin Assemblies and Dystonia Movement Disordersmentioning
confidence: 99%